Cut-Score Operating Function Extensions: Penalty-Based Errors and Uncertainty in Standard Settings. Issue 7 (October 2021) - Grabovsky, Irina; Pace, Jesse; Runyon, Christopher
We model pass/fail examinations aiming to provide a systematic tool to minimize classification errors. We use the method of cut-score operating functions to generate specific cut-scores on the basis of minimizing several important misclassification measures. The goal of this research is to examine the combined effects of a known distribution of examinee abilities and uncertainty in the standard setting on the optimal choice of the cut-score. In addition, we describe an online application that allows others to utilize the cut-score operating function for their own standard settings.